Green Supply Chain Emission Reduction Strategies and Smart Contracts Under Blockchain Technology - WANG Xin, WANG Yasheng, ZHANG Shuhua, WANG Xinyu, XU Shuai (Jisuanji kexue yu tansuo, 2024)
Under the background of “double carbon”, the concept of green consumption has been deeply rooted in the hearts of people. However, consumers do not fully trust the greenness of products. The information transparency and traceability mechanism of blockchain technology can well dispel consumers?? doubts. Introducing blockchain technology into traditional green supply chains, considering consumer green preferences and green trust, a game model is constructed among members of the green supply chain before and after the application of blockchain technology, as well as under different power structures, to quantitatively study their emission reduction and pricing strategies, and to explore how to achieve optimal consumer surplus and total social welfare. On the basis of adopting blockchain technology, smart wholesale price contracts and cost sharing smart contracts are designed, and the reasonable range of smart wholesale prices and the optimal cost sharing ratio are calculated, to improve enterprise operational efficiency and achieve supply chain coordination. The results show that when consumers?? green preference is high, the use of blockchain can bring more benefits to all participants in the supply chain. At the same time, the higher the willingness of consumers to buy green products, the greater the benefits. Through numerical analysis, it is found that the smart contracts can better coordinate the supply chain in the case of retailers leading the supply chain. Finally, the validity of the relevant conclusions is verified through empirical cases.